Making Histories and Narrating Things: Histories of Handmade Objects in Two Indigenous Communities - MacDonald, Katya Claire (University of Saskatchewan, 2017)
Building on and deepening my existing community-engaged research relationships with community members in Sliammon, B.C. and Ile-a-la-Crosse, SK, this dissertation is, as I described it to community members, a history of handmade items. At the intersection of economic change, changing colonialist policy, ideas about tradition, and Indigenous political interests that has taken place in Indigenous communities in the latter half of the twentieth century, seemingly local or domestic objects in fact highlight complexities within and beyond communities over time. The role of objects was shaped – in conflicting or paradoxical ways – by newcomer institutions that sought to define Indigenous people and their activities in constrained ways. Yet for community members, the processes and products of making things became ways to define and historicize tradition itself. These two themes – objects in families and communities, and objects in newcomer institutions – provide the overarching structure for this dissertation. People in both communities have shared in parallel processes of using and co-opting colonizing influences not only to make a living for themselves within those contexts, but also, through their involvement in “making things,” to make explicit statements about the significance of histories and historical interpretation in community changes. This dissertation, and the individual and collective experiences of making things portrayed within it, are a means of discussing how labour, gender, and tradition have been mobilized in Ile-a-la-Crosse and Sliammon in the twentieth century, and especially from the 1930s and onwards to respond to contemporary realities. Because the communities I have worked with are very different places from each other – a small, west coast First Nation and a predominantly Metis municipality in northwestern Saskatchewan – this work is intentionally not comparative. Rather, I use these two case studies to follow how community members have interpreted their histories through processes of making tangible “things,” depending on local historical circumstances. I consider the changing ways that community members have responded to and worked within colonial intervention. First and foremost, though, by making things, they sought to address their own economic, social, and political concerns. Changes in processes of making and interpreting handmade items help to illuminate how community members envisioned objects in their communities, not only as practical items or symbols of cultures or histories, but also as ways to describe the shifting significance of tradition for making sociopolitical arguments illustrated by the objects themselves.